اسلامی اخلاقی اصولوں کی روشنی میں صنفی مساوات اور انصاف کا فروغ: Advancing Gender Justice and Equality through the Ethical Framework of Islamic Principles - Syed Hamid Ali Shah; Dr. Jawwad Haider Hashmi (Al-Amīr Research Journal for Islamic Studies, 2024)
The issue of gender differences has been debated in human societies since ancient times. Different religions and cultures have raised the question of whether men are superior to women or vice versa. The roots of this difference are actually embedded in the laws, customs, and social traditions that establish certain distinctions between men and women. Islamic teachings also contain specific rulings, such as those related to jihad, dowry, hijab, testimony, and divorce, where differences between men and women can be found. At first glance, this distinction may raise doubts in some minds about the existence of gender discrimination in Islam; however, the reality is quite the opposite. Islam is a religion that bases its laws and rulings not on gender differences but on justice and fairness. These differences do not reflect superiority or inferiority of one gender over another but have been designed considering the natural, physical, and spiritual composition of both men and women. In Islam, equity is adopted as a fundamental principle instead of equality because true justice means granting each individual their rights according to their natural abilities, responsibilities, and status. Therefore, the difference in the rights and duties of men and women does not imply that one is superior to the other; rather, their true superiority is determined by their character, actions, and moral standards. In today’s world, it is essential to explain the differences between men and women in Islamic teachings along with their original wisdom so that the new generation can understand that in Islam, gender differences are merely a form of division of labor rather than a symbol of superiority of one gender over another. With this need in mind, this article aims to clarify through research and descriptive methods that the foundation of Islamic laws is based not on gender differences but on justice and fairness. Keywords: Islam, men, women, gender, differences, equity, principles.